Anaesthetic management of a patient with hypertrophic obstructive cardiomyopathy undergoing laparoscopic cholesytectomy - Gautam, Binod; Bhochhibhoya, Anisha (Journal of Kathmandu Medical College, 2018)
Hypertrophic cardiomyopathy is a genetic disorder characterized by asymmetric left ventricular hypertrophy with or without left ventricular outflow tract obstruction. From asymptomatic state to sudden death comprise its varied clinical range. Owing to complex patho-physiology and very high risk of cardiac events, its peri-operative management demands meticulous maintenance of hemodynamic parameters. Prevention and prompt correction of factors such as hypovolemia, tachycardia, and increased contractility that can exacerbate the left ventricular outflow obstruction, arrhythmias and myocardial ischemia are essential for improving patient outcome. Laparoscopic surgeries in these patients can further amplify anaesthetic concerns and add to the challenges. A 58 year female was scheduled for surgery having suffered frequent complications of cholelithiasis. As there is paucity of reports evaluating laparoscopic surgery, we report this patient diagnosed with hypertrophic obstructive cardiomyopathy, who received general anaesthesia to undergo laparoscopic cholecystectomy successfully without suffering complications during surgery and hospital stay.